PENGARUH UKURAN PERUSAHAAN, KESULITAN KEUANGAN/ FINANCIAL DISTRESS, KOMITE AUDIT, KEPEMILIKAN INSTITUSIONAL, KEPEMILIKAN MANAJERIAL DAN PROPORSI DEWAN KOMISARIS INDEPENDEN TERHADAP INTEGRITAS LAPORAN KEUANGAN PADA PERUSAHAAN JASA KEUANGAN YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2012-2014 - Ariantoni, Zendra; Nasir, Azwir; Haryani, Eka (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2017)
The purpose of this study was to determine the effect firm size, financial distress, the audit committee, institutional ownership, managerial ownership and the proportion independent board for the integrity of the financial statements on a financial services company listed the Indonesia Stock Exchange in 2012-2014. The population of this research is financial services company (excluding banking company) listed on the Indonesia Stock Exchange in 2012-2014 total of 39 companies, the sampling technique using purposive sampling so that the eligible sample are 31 companies. Data analysis method used multiple linear regression analysis using SPSS 21 for windows. Result of research can be concluded that the variable size of the company, financial distress, the audit committee of institutional ownership affect the integrity of the financial statements of financial services firms because tcount institutional ownership is greater than t table. While managerial ownership variable eliminated from the data processing because it shows constant value. Variabel proportion of independent board does not affect the integrity financial statements of the company for financial services company t count size smaller than t table.Keyword: company size, financial distress, the audit committee, institutional ownership